Synthesis and in vitro evaluation of N-alkyl-7-methoxytacrine hydrochlorides as potential cholinesterase inhibitors in Alzheimer disease - Korabecny, Jan; Musilek, Kamil; Holas, Ondrej; Binder, Jiri; Zemek, Filip; Marek, Jan; Pohanka, Miroslav; Opletalova, Veronika; Dohnal, Vlastimil; Kuca, Kamil (Bioorganic & medicinal chemistry letters, 2010)
All approved drugs for Alzheimer disease (AD) in clinical practice ameliorate the symptoms of the disease. Among them, acetylcholinesterase inhibitors (AChEIs) are used to increase the cholinergic activity. Among new AChEI, tacrine compounds were found to be more toxic compared to 7-MEOTA (9-amino-7-methoxy-1,2,3,4-tetrahydroacridine). In this Letter, series of 7-MEOTA analogues (N-alkyl-7-methoxytacrine) were synthesized. Their inhibitory ability was evaluated on recombinant human acetylcholinesterase (AChE) and plasmatic human butyrylcholinesterase (BChE). Three novel compounds showed promising results towards hAChE better to THA or 7-MEOTA. Three compounds resulted as potent inhibitors of hBChE. The SAR findings highlighted the C(6)-C(7)N-alkyl chains for cholinesterase inhibition.
Keywords: Cholinesterase Inhibitors; Recombinant Proteins; Structure-Activity Relationship; takrin; Alzheimerova nemoc; Alzheimer Disease; Inhibitory Concentration 50; acetylcholinesterasa; molekulární modely; vztahy mezi strukturou a aktivitou; rekombinantní proteiny; Models, Molecular; lidé; Humans; Butyrylcholinesterase; inhibiční koncentrace 50; butyrylcholinesterasa; Tacrine; Acetylcholinesterase; cholinesterasové inhibitory